Design, Synthesis, Biological Evaluation and Molecular Dynamic Study of Oxadiazole Containing Some Novel Schiff Bases - Komal vitthal Gadhe; Manoj G. Damale; Rashmi S. Chouthe; Harshali A. Takale; Santosh D. Shelke; Mohd. Usman Mohhasiddique (International Journal of Scientific Research in Chemistry, 2025)
Microbial resistance remains a significant risk and a prominent cause of death worldwide, although massive attempts were made to control infections. In an effort to develop biologically active antimicrobial agents in present study we have reported design, synthesis & biological evaluation and molecular dynamic study of oxadiazole containing novel Schiff bases. In order to increase biological activity and improve drug-likeness, oxadiazole moieties were purposefully added to Schiff base frameworks using bioisosteric replacement principle .The 1, 3, 4-oxadiazole moiety were used to design near about 100 derivatives, online tool FAFDrug4 were used to evaluate the drug-likeness screening. Molecular docking study was performed for their possible inhibitory action on microrgsnism using the PyRx software. The final Schiff base derivatives were obtained by condensation with different aromatic aldehydes with oxadiazole moiety by using zinc chloride as a catalyst the synthesis was performed by microwave irradiation.the present practical yield of obtained Schiff bases are ranging form 70-80%. The structures of the synthesized compounds were confirmed using spectroscopic techniques. The in vitro antimicrobial activity of the synthesized oxadiazole-based Schiff bases was evaluated against selected microbial strains..the top ten Schiff base have exacellaent antifungal activity and moderate antibacterial activity. the Schiff bases VKG-30 and VKG-70 demonstrated moderate antibacterial activity .Furthermore molecular dynamics simulations were also conducted to assess the stability and behavior of ligand-receptor complexes for that VKG-70 schiff bases and dhn protein was used. The integration of synthetic chemistry with computational tools provides valuable insight into the structure-activity relationships of these novel oxadiazole-Schiff base hybrids, offering promising leads for future drug development.